Sialic acid-binding immunoglobulin-like lectin 9 as a potential therapeutic target for chronic obstructive pulmonary disease. Issue 7 (5th April 2021) - Chen, Zi; Xu, Shuang-Lan; Ge, Lin-Yang; Zhu, Jin; Zheng, Tao; Zhu, Zhou; Zhou, Linfu
Abstract : Abstract: Chronic obstructive pulmonary disease (COPD) has become the third-leading cause of death worldwide, which is a severe economic burden to the healthcare system. Chronic bronchitis is the most common condition that contributes to COPD, both locally and systemically. Neutrophilic inflammation predominates in the COPD airway wall and lumen. Logically, repression of neutrophilia is an essential fashion to COPD treatment. However, currently available anti-neutrophilic therapies provide little benefit in COPD patients and may have serious side effects. Thus, there is an urgent need to explore an effective and safe anti-neutrophilic approach that might delay progression of the disease. Sialic acid-binding immunoglobulin-like lectin (Siglec)-9 is a member of the Siglec cell surface immunoglobulin family. It is noteworthy that Siglec-9 is highly expressed on human neutrophils and monocytes. Ligation of Siglec-9 by chemical compounds or synthetic ligands induced apoptosis and autophagic-like cell death in human neutrophils. Furthermore, administration of antibody to Siglec-E, mouse functional ortholog of Siglec-9, restrained recruitment and activation of neutrophils in mouse models of airway inflammation in vivo . Given the critical role that neutrophils play in chronic bronchitis and emphysema, targeting Siglec-9 could be beneficial for the treatment of COPD, asthma, fibrosis, and related chronic inflammatory lung diseases.